The 2020 Larsen C Ice Shelf surface melt is a 40-year record high - Suzanne Bevan (The Cryosphere, 2020)
Along with record-breaking summer air temperatures at an Antarctic Peninsula meteorological station in February 2020, the Larsen C ice shelf experienced an exceptionally long and extensive 2019/2020 melt season. We use a 40-year time series of passive and scatterometer satellite microwave data, which are sensitive to the presence of liquid water in the snow pack, to reveal that the extent and duration of melt observed on the ice shelf in the austral summer of 2019/2020 was the greatest on record. We find that unusual perturbations to Southern Hemisphere modes of atmospheric flow, including a persistently positive Indian Ocean Dipole in the spring and a very rare Southern Hemisphere sudden stratospheric warming in September 2019, preceded the exceptionally warm Antarctic Peninsula summer. It is likely that teleconnections between the tropics and southern high latitudes were able to bring sufficient heat via the atmosphere and ocean to the Antarctic Peninsula to drive the extreme Larsen C Ice Shelf melt. The record-breaking melt of 2019/2020 brought to an end the trend of decreasing melt that had begun in 1999/2000, will reinitiate earlier thinning of the ice shelf by depletion of the firn air content, and probably affected a much greater region than Larsen C Ice Shelf.